Implementing just climate adaptation policy: An analysis of recognition, framing, and advocacy coalitions in Boston, U.S.A. - Malloy, Jeffrey T.; Ashcraft, Catherine M.; Kirshen, Paul; Safford, Thomas G.; Aytur, Semra A.; Rogers, Shannon H. (Frontiers in Sustainable Cities, 2022)
Cities face intersectional challenges implementing climate adaptation policy. This research contributes to scholarship dedicated to understanding how policy implementation affects socially vulnerable groups, with the overarching goal of promoting justice and equity in climate policy implementation. We apply a novel framework that integrates social justice theory and the advocacy coalition framework to incrementally assess just climate adaptation in Boston, Massachusetts in the United States. Boston made an ambitious commitment to address equity as part of its climate planning and implementation efforts. In this paper, we evaluate the first implementation stage over the period 2016–2019 during which Boston developed coastal resilience plans for three neighborhoods. Despite Boston's commitment to equity, we find injustice was nevertheless reproduced through representation and coalition dynamics, the framing of problems and solutions, and a failure to recognize the priorities and lived experiences of city residents. The assessment framework presented can be adapted to evaluate how other climate adaptation initiatives advance social justice and highlights the need for incremental evaluation over short time periods to inform ongoing implementation efforts.